Nonlinear Finite Element Analysis of Reinforced Concrete Beams Strengthened with Externally Bonded Steel Plate using ANSYS - Abdulkadir, Mohamed Raouf; Aziz, Zana Abdalla; Muhammad, Jaza Hassan (Sulaimani Journal for Engineering Sciences, 2017)
The present work presents a numerical study to simulate the behavior of reinforced concrete beams strengthened with steel plates. The study is carried out using two un-strengthened RC beams and two RC beams strengthened with (1mm, and 3mm) steel plates. The beams are modeled and analyzed by nonlinear FEM using ANSYS v14.5. The numerical results are in good agreement with experimental load-displacement curves and ultimate load carrying capacity.
Keywords: Beam; strengthening; steel plates; ANSYS